2019
DOI: 10.18632/aging.102354
|View full text |Cite
|
Sign up to set email alerts
|

Decreased RIPK1 expression in chondrocytes alleviates osteoarthritis via the TRIF/MyD88-RIPK1-TRAF2 negative feedback loop

Abstract: Osteoarthritis (OA) is the most common degenerative joint disease and involves the loss of articular cartilage integrity, formation of articular osteophytes, remodeling of subchondral bone, and synovitis. Knockdown of receptor interacting serine/threonine kinase (RIPK) 1 leads to anti-inflammatory and anti-apoptotic effects. However, the involvement of RIPK1 in the pathogenesis of OA is unclear. Here, we evaluated the effect of RIPK1 on chondrocytes and elaborated the underlying molecular mechanism. Knockdown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 55 publications
2
10
0
Order By: Relevance
“…Multiple studies have shown that subchondral bone plays a critical role in the occurrence and development of OA [35,36]. Remodeling of subchondral bone is an important part of the progression of OA [37,38]. Nakasa et al [39] showed that subchondral sclerosis of the tibia could be observed 7 days after DMM, which was consistent with the findings of our study.…”
Section: Discussionsupporting
confidence: 91%
“…Multiple studies have shown that subchondral bone plays a critical role in the occurrence and development of OA [35,36]. Remodeling of subchondral bone is an important part of the progression of OA [37,38]. Nakasa et al [39] showed that subchondral sclerosis of the tibia could be observed 7 days after DMM, which was consistent with the findings of our study.…”
Section: Discussionsupporting
confidence: 91%
“…Multiple studies have shown that subchondral bone plays a critical role in the occurrence and development of OA [35,36]. Remodeling of subchondral bone is an important part of the progression of OA [37,38]. Nakasa T et al [39] showed that subchondral sclerosis of the tibia could be observed 7 days after DMM, which was consistent with the findings of our study.…”
Section: Discussionsupporting
confidence: 91%
“…The NF-кB pathway promoted the expression of OArelated proteins, such as RUNX2 and VEGF 17,18,20,34 . Many studies have confirmed that MYD88 played an important role in the OA process in recent years [35][36][37][38][39] . Here, modulation of miR-665 and circRNF121 resulted in altered MYD88 expression.…”
Section: Discussionmentioning
confidence: 91%